Stroke prevention in patients with acute ischemic stroke and atrial fibrillation in Germany - a cross sectional survey - Wutzler, Alexander; Veltkamp, Roland (BMC neurology, 2019)
Atrial fibrillation (AF) is present in 15-20% of patients with acute ischemic stroke. Oral anticoagulation reduces the risk of AF-related recurrent stroke but clinical guideline recommendations are rather vague regarding its use in the acute phase of stroke. We aimed to assess the current clinical practice of medical stroke prevention in AF patients during the acute phase of ischemic stroke.